Situationally influenced tinnitus coping strategies: a mixed methods approach - Beukes, Eldre W.; Manchaiah, Vinaya; Andersson, Gerhard; Allen, Peter M.; Terlizzi, Paige M.; Baguley, David M. (Taylor & Francis Online, 2017)
Purpose: The primary aim of this study was to identify coping strategies used to manage problematic tinnitus situations. A secondary aim was to determine whether different approaches were related to the level of tinnitus distress, anxiety, depression, and insomnia experienced. Materials and methods: A cross-sectional survey design was implemented. The study sample was adults interested in undertaking an Internet-based intervention for tinnitus. Self-reported measures assessed the level of tinnitus distress, depression, anxiety, and insomnia. An open-ended question was used to obtain information about how problematic tinnitus situations were dealt with. Responses were investigated using qualitative content analysis to identify problematic situations. Further data analysis comprised of both qualitative and quantitative methods. Results: There were 240 participants (137 males, 103 females), with an average age of 48.16 years (SD: 22.70). Qualitative content analysis identified eight problematic tinnitus situations. Participants had either habituated to their tinnitus (7.9%), used active (63.3%), or passive (28.8%) coping styles to manage these situations. Those who had habituated to tinnitus or used active coping strategies had lower levels of tinnitus distress, anxiety, and depression. Conclusions: The main problematic tinnitus situations for this cohort were identified. Both active and passive coping styles were applied to approach these situations. The coping strategies used most frequently and utilised in the widest range of problematic situations were using sound enrichment and diverting attention. Implications for Rehabilitation. The main problematic tinnitus situations for this group of participants were identified. Overall, a limited range of strategies were used to deal with individual problematic situations. The use of sound enrichment and diverting attention was applied in the widest range of problematic situations.